PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Ginting, Pernandus; Sebayang, Minda Muliana (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The purpose of this research is to test and analyze the effect of partial profitability on company value, to test and analyze the effect of dividend policy partially on company value, to test and analyze the effect of partial debt policy on company value and to test and analyze the effect of profitability, dividend policy and debt policy simultaneously on company value in Food and Beverage Sub-Sector manufacturing companies listed on the Indonesia Stock Exchange 2019-2023. The population in this study was 24 companies in the Food and Beverage Sub Sector listed on the IDX and the sample from research on Food and Beverage Sub Sector Companies was 8 companies with 5 years of observation. The data collection technique used in this research is documentation. The analysis techniques used in this research are descriptive statistics, Multiple Linear Regression analysis, Partial Test, Determinant Test. The research results show that partially Profitability has a positive and significant effect on Company Value, partially Dividend Policy has no effect on Company Value, partially Debt Policy has a positive and significant effect on Company Value and simultaneously shows that Profitability, Dividend Policy and Debt Policy have a significant effect on Company Value in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesian Stock Exchange 2019-2023.